Advancing project stakeholder analysis by the concept 'shadows of the context'. Issue 1 (January 2018) - Eskerod, Pernille; Larsen, Tina
Abstract: The paper contributes to the theoretical debate on stakeholder management within project-oriented organizations. Despite acknowledging that 'no project is an island', project management theory (being originally a child of Scientific Management) has drawn on reductionism, i.e. the practice of simplifying the description of a complex phenomenon in order to better grasp it. Project stakeholder management theory has been heavily influenced by this approach, and the unintended consequence is that the simplicity of the stakeholder conceptualization makes it difficult for project representatives to predict stakeholder behavior. In the paper, we suggest the concept 'shadows of the context' as a substitute for narrow perceptions of 'What's in it for me?'. Advantages and disadvantages of a reductionist approach versus the richer and more profound and holistic 'shadows of the context' approach within stakeholder analysis are discussed. The paper also celebrates Prof. J. Rodney Turner's significant influences within the project management field. Highlights: This conceptual paper offers an alternative to a reductionist approach within PM. The concept 'shadows of the context' for project stakeholder analysis is proposed. The concept will help to better understand and predict stakeholder behavior. Two methods to operationalize the 'shadows of the context' are presented. The paper includes a tribute to IJPM's chief editor, professor J. Rodney Turner.